(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Halal does not simply indicate a product as edible for not being prohibited by shariah, but should encompass the meaning of tayyib (good), i.e. clean, hygienic, safe, of good quality and not being harmful. Therefore, the need in Muslim society for products that are merely halal is insufficient, instead it is necessary to truly understand and apply the concept of halalan tayyiban (halal and good). The aspect of halal, particularly for food products, is guaranteed under the Malaysian legal framework through legal and institutional mechanisms. This article elaborates on the concept of halalan tayyiban from the shariah perspective, and subsequently relates it to the relevant laws. The writers conclude that the concept of halalan tayyiban exists and is applied through various laws. Keywords: halal, law, shariah, food, product, halalan tayyiba